Elevated Serum Levels of Osteopontin in Patients with Psoriasis: Is It Associated with Ocular Comorbidities? - Elsadek, Hala M.; Kamel , Radwa O. M.; Elsaid, Marwa Abdallah; Rashed, Rasha Muhammad; Ali, Mona S. (Dermatology Practical & Conceptual, 2024)
Introduction: Psoriasis is a chronic inflammatory disease affecting 2%-3% of the global population via immune-mediated mechanisms. Osteopontin plays a crucial role in T-helper 1 and T-helper 17-mediated illnesses, including psoriasis. Ocular complications in psoriasis have been reported and their assessment is of importance. Osteopontin is normally expressed constitutively in ocular structures and is linked to ocular homeostasis.Objective: This study aimed to clarify the role of osteopontin (OPN) in psoriasis (PS) and its correlation with disease severity and ocular manifestations.  Methods: A case-control study involving 40 psoriatic patients and an equal number of age and sex-matched healthy subjects was conducted. We used the psoriasis area severity index (PASI) to assess disease severity and performed a comprehensive ophthalmological examination. Additionally, we measured serum osteopontin levels using Enzyme-Linked Immunosorbent Assay (ELISA) in both groups.Results: A significant elevation in serum OPN levels in psoriatic patients compared to controls was found (P=0.00). Furthermore, there was a highly significant positive correlation between serum OPN levels and patient age, disease duration, and PASI scores. Notably, a higher prevalence of ocular complications, including blepharitis, corneal affection, conjunctivitis, keratoconjunctivitis sicca, and cataract, in psoriatic patients compared to controls was observed. Importantly, significant associations between serum OPN levels and the presence of cataracts and intraocular pressure (IOP) were identified. Additionally, significant correlations between serum OPN levels and measures of visual acuity and ocular surface health were found.Conclusions: Osteopontin is considered a marker of psoriasis severity and is associated with ocular comorbidities in psoriasis.